Hitting our Heads on the Glass Ceiling: Women and Leadership in Education in Indonesia - Dzuhayatin, Siti Ruhaini; Edwards, Jan (Studia Islamika, 2010)
This paper begins by describing the present situation at the madrasah level in areas that participate in LAPIS-ELOIS activities and identifies the personal, cultural, and religious factors that contribute to women's under-representation in leadership and decision-making roles. Women's participation in leadership and decision making in Islamic universities involved in LAPIS-PGMI is discussed using data from consortium institutions. The range of factors contributing to the imbalance are discussed before turning to the policy issues that continue to contribute to gender disparity in leadership and decision making. The paper concludes by identifying some directions for action.DOI: 10.15408/sdi.v17i2.460